The effect of amlodipine on blood glucose level and its interaction with oral hypoglycemic drugs in albino rabbits - Prajapat, Rajeev; Jain, I. P.; Singh, S. P.; Singh, Suresh; Agarwal, Pooja (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Amlodipine used as many cardiac conditions esp in hypertension. Diabetes affects cardiovascular system adversely. So this study was done to see effect of amlodipine on blood glucose level and its interaction with commonly used oral hypoglycemic agents in diabetic & non diabetic albino rabbits. Methods: Rabbits were divided into nine groups of 6 rabbits in each group. I and II group were non-diabetic given normal saline and amlodipine respectively. Group III to IX were made diabetic by using alloxan monohydrate (150mg/kg i.p.) & given normal saline, glimepiride, metformin, pioglitazone, amlodipine + glimepiride, amlodipine + metformin and amlodipine + pioglitazone respectively. All drugs were given orally once daily for 7 day except group VII, VIII and IX in which glimepiride, metformin and pioglitazone were added on 7th day. After GTT blood glucose level were measured at 0, 1, 2 and 6 hours on 7th day in all groups by using spectrophotometer. Results: After 7 days of treatment the amlodipine produced significant hyperglycemia in normal rabbits. Amlodipine on combination, causes significant decreased in hypoglycemic effect of glimepiride, significant increased the hypoglycemic effect of metformin, while no significant changes in hypoglycemic effects of pioglitazone in diabetic rabbits. Conclusion: The present study shows that amlodipine causes hyperglycemia in normal rabbits. Amlodipine significantly altered hypoglycemic effect of glimepiride and metformin as compared to control group. If these finding are true to human beings then amlodipine should be use cautiously in diabetic patient on oral hypoglycemic drugs.